BRIDGING HEALTHCARE DIVIDES: A HISTORICAL ANALYSIS AND FUTURE STRATEGIES FOR NORTH-SOUTH COLLABORATION IN PUBLIC HEALTH INITIATIVES IN INDIA - S. R., Divya; Dilip, Divya Grace (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Healthcare Divide in India refers to the significant regional differences in healthcare nationwide. This encompasses variations in healthcare infrastructure, accessibility, service delivery, and health outcomes between regions, particularly North and South India. The divides stem from resource allocation, socioeconomic dynamics, cultural practices, and governance structures. Recognising and addressing these divides is crucial for developing inclusive healthcare policies and advocacy efforts should aim to influence policymakers to implement inclusive and regionally sensitive healthcare policies, ensuring equitable access and improved health outcomes for all citizens. The healthcare divide in India is a complex issue, with stark disparities between North and South regions. This divide encompasses variations in healthcare infrastructure, accessibility, service delivery, and health outcomes.